2014
DOI: 10.3109/13880209.2013.872153
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indicaextract–artesunic acid combination produces an increased cure rate ofPlasmodium berghei-infected mice

Abstract: (Meliaceae).Objective: Combination of an artemisinin-based compound and a medicinal herb extract will provide an indigenous alternative/herb-based ACT. Materials and methods: The in vivo schizontocidal activity of the crude aqueous extract of 100, 500, and 1000 mg/kg of A. indica fresh leaves (NCE) and 6, 15, and 20 mg/kg of artesunic acid were determined, alone and in combination, while keeping the dose of artesunic acid constant at 15 mg/kg, using the Peter's 4-day suppressive test and Swiss albino mice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Therefore, there is an urgent need for innovative and alternative strategies to combat the resistant strains of the parasite. Some studies have shown that plant-based preparations, co-administered with orthodox drugs, produced better antimalarial activities on both chloroquine (CQ)-sensitive and CQ-resistant Plasmodium strains (Ahorlu et al 1997;Muregi et al 2003Muregi et al , 2007Adibe 2009;Anagu et al 2014). MAMA decoction (MD), an herbal remedy prepared from a mixture of the leaves of Mangifera indica L. (Anacardiaceae), Alstonia boonei De Wild (Apocynaceae), Morinda lucida Benth (Rubiaceae) and Azadirachta indica A. Juss (Meliaceae) in equal proportions, has been reported to possess antimalarial activities on CQ-sensitive P. berghei NK65 in rodents with acceptable safety (Akanmu et al 2013;Adepiti et al 2014;Odediran et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need for innovative and alternative strategies to combat the resistant strains of the parasite. Some studies have shown that plant-based preparations, co-administered with orthodox drugs, produced better antimalarial activities on both chloroquine (CQ)-sensitive and CQ-resistant Plasmodium strains (Ahorlu et al 1997;Muregi et al 2003Muregi et al , 2007Adibe 2009;Anagu et al 2014). MAMA decoction (MD), an herbal remedy prepared from a mixture of the leaves of Mangifera indica L. (Anacardiaceae), Alstonia boonei De Wild (Apocynaceae), Morinda lucida Benth (Rubiaceae) and Azadirachta indica A. Juss (Meliaceae) in equal proportions, has been reported to possess antimalarial activities on CQ-sensitive P. berghei NK65 in rodents with acceptable safety (Akanmu et al 2013;Adepiti et al 2014;Odediran et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on antimalarial drug combination showing their in vitro and in vivo on malaria parasites [4145]. The aqueous crude extracts of G. pentaphyllum and M. oleifera leaves exhibited high level of antimalarial activity in P. berghei -infected mice when administered with artesunate.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, oxidative damage in order to inhibit malaria parasite of artemisinin has been reported, and might related to antimalarial property of Siamese neem tree extract. Moreover, it has been reported antimalarial activity was found in either A. indica leaf extract alone or in combination with artesunate in dosedependent manners [28]. Azadirachtin and nimbin were considered to be active compounds in this extract [29,30].…”
Section: Discussionmentioning
confidence: 99%